Comparative study of two thoracic segmental spinal anaesthesia techniques for laparoscopic cholecystectomy: low-dose hypobaric ropivacaine and isobaric ropivacaine at T10-11 intervertebral space vs. standard technique using isobaric levo bupivacaine at T8-T10 intervertebral space - Nagar, Sachin; Paliwal, Naresh; Lohia, Robin; Saluja, Vivek; Dutt, Narender (International Journal of Clinical Trials, 2024)
Background: Many prior studies have utilized thoracic or lumbar spinal anesthesia with isobaric/hyperbaric bupivacaine or Ropivacaine and opioids for laparoscopic cholecystectomy and have reported variable results. our study is centered around addressing the occurrence of intraoperative right shoulder pain and its potential impact on the need for conversion to general anesthesia. Methods: This is a prospective comparative case series study in which 70 patients scheduled for elective laparoscopic cholecystectomy were. Patients in Group R received 1 ml (1 mg) of Hypobaric Ropivacaine 0.1% at T10-11 followed by 25 mcg fentanyl, and 5 mg Isobaric Ropivacaine 0.5% whereas patients in Group B received 1.5 ml (7.5 mg) Isobaric levo Bupivacaine 0.5% and 25 mcg fentanyl at T8-T10. Patients in both the groups were compared for incidence of shoulder tip pain and Hemodynamic stability. Results: Both techniques achieved satisfactory anaesthesia quality, with similar results in surgical anaesthesia onset. Average surgical duration was 45-75 minutes with average of 60 mins with longer durations in two cases common to both the groups. In group R there was there was no bradycardia or hypotension recorded more than 10% of preinduction vitals. Whereas in group B 2 patients had bradycardia and hypotension more than 10% of preinduction vitals. Conclusions: The T10-11 technique using low-dose (6 mg) hypobaric ropivacaine and isobaric Ropivacaine appears to be superior in terms of shoulder tip pain, and hemodynamic stability compared to the T8-T10 technique using isobaric levo-Bupivacaine alone in higher dose.